Research progress in modulating the auditory system by the cochlear circadian clock system in response to noise exposure - Song, Xiaoqiong; Cheng, Mengzhu; Gu, Cui; Wang, Fenghan; Ma, Kefeng; Wang, Chunping; She, Xiaojun; Cui, Bo (Frontiers in Neuroscience, 2025)
The circadian clock is an endogenous system evolved to adapt to environmental changes. Recent studies confirmed that the cochlea exhibits circadian oscillations regulating auditory function. These oscillations are linked to brain-derived neurotrophic factor and glucocorticoid levels. Circadian rhythms influence cochlear sensitivity to noise by regulating the secretion of brain-derived neurotrophic factors and glucocorticoids. This study explores the regulatory mechanism of the circadian clock system, its impact on the auditory system, and its potential role in noise-induced hearing loss. Understanding the regulatory mechanisms of circadian rhythms in auditory function will provide new ideas for developing treatments for noise-induced hearing loss.